New Thylacocephala (Crustacea) assemblage from the Spathian (Lower Triassic) of Majiashan (Chaohu, Anhui Province, South China). (March 2021) - Ji, Cheng; Tintori, Andrea; Jiang, Dayong; Motani, Ryosuke; Confortini, Federico
Abstract: Here we report and describe a new assemblage of Thylacocephala (Crustacea) from the late Spathian (Early Triassic) of Chaohu, Anhui Province, South China. The assemblage consists of at least three species from different genera: the small-sized Microcaris rectilineatus n. sp. appears the most abundant, while the large-sized Ankitokazocaris sp. and Diplacanthocaris chaohuensis n. gen. n. sp. are rare. A morphometric analysis of the carapace outline separates Diplacanthocaris chaohuensis n. gen. n. sp. from other genera. Along with Ankitokazocaris chaohuensis Ji et al., 2017 and Kitakamicaris sp. from the horizon 28 m above this assemblage, four different genera of Thylacocephala occur in the Chaohu Fauna. With additional materials reported from Japan and North America, the Early Triassic is now known as the period when Thylacocephala reached their highest diversity and widest geographical distribution. Thylacocephala quickly diversified shortly after the Permian–Triassic mass extinction, probably because of their ability to survive in a relatively low-oxygen environment. Thylacocephalan fossils from Chaohu are found in dense concentrations, suggesting they might have constituted a food source for the fishes and marine reptiles in the Chaohu Fauna. UUID: http://zoobank.org/b24e82a7-ea9a-49dc-9c6c-8ad8262db276